The Relevance of iBox Store Atmosphere: Building Customer Satisfaction and Loyalty (International Journal of Scientific Research and Management (IJSRM), 2023)
The rapid development of information technology triggers the growth of competition between gadget stores in Indonesia. Each competing store offers attractiveness for customers, one of which is iBox. A comfortable store atmosphere with unique and creative decorations is the key for businesses to attract consumers to visit. Creating a store atmosphere through visuals, arrangement, light, music, and aroma can create a comfortable buying environment to influence consumer perceptions and emotions in determining customer satisfaction and loyalty. This study aimed to determine the effect of the Store Atmosphere on Customer Satisfaction and its Implications for Customer Loyalty at IBox Indonesia. The research data collection method used a questionnaire of 211 respondents through purposive sampling, analysed using Structural Equation Modeling (SEM) with AMOS 24 tools.